Pediatric Cushing’s Disease and Pituitary Incidentaloma: Is This a Real Challenge? - Rosa Maria Paragliola; Pietro Locantore; Alfredo Pontecorvi; Salvatore Maria Corsello (Case Reports in Endocrinology)
Cushing’s disease (CD) is the most common cause of endogenous Cushing’s syndrome in children and adolescents and represents a rare cause of short stature. A 14-year-old boy came to our attention for progressive weight gain and short stature. At examination, height was 140 cm (3rd centile) and weight was 37.7 kg (10th centile). Tanner stage was G2, PH 3, testis 3 mL. Hypothyroidism and growth hormone deficiency were excluded. A marked increase of urinary free cortisol, a nonsuppressible serum cortisol after Liddle 1 test, and an elevated ACTH value confirmed the diagnosis of ACTH dependent Cushing’s syndrome. Pituitary magnetic resonance imaging (MRI) showed a left microadenoma and a right focal area of lesser enhancement. Therefore, bilateral inferior petrosal sinus sampling (BIPSS) with CRH stimulation was performed to obtain an accurate preoperative localization of the adenoma: the interpetrosal sinus ACTH gradient indicated lateralization of ACTH secretion to the left side. The patient underwent transsphenoidal surgery with selective microadenomectomy, with an immediate ACTH decline in the postoperative phase. Histology confirmed the diagnosis of corticotrophic pituitary adenoma. Glucocorticoid replacement therapy was instituted. Clinical examination demonstrated a rapid catch-up growth (10th centile), with a normalization of body mass index and an adequate pubertal development.